Gas in the Kidney (Emphysematous Pyelonephritis) often Misdiagnosed as Colonic Gas - Zulkifl, Mohammad Ali; Alam, Mir Rasekh (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Emphysematous pyelonephritis (EPN) is a serious and often life threatening infection of the renal and perirenal tissues. The characteristic feature of this infection is the presence of gas within the kidney and perinephric tissues. EPN usually occurs in diabetic women. CT Scan is the investigation of choice not only to establish the diagnosis but also to plan the line of management. Renal preservation must be the aim of management. This can be achieved to a great extent by medical management combined with percutaneous drainage of obstructed kidney. However nephrectomy is indicated in life threatening infection of the kidney. Prompt diagnosis and the timing of drainage could be the prognostic factor. A case of EPN in a diabetic patient who was successfully managed by nephrectomy is presented. J Bangladesh Coll Phys Surg 2015; 33(2): 91-94